Utilization and examination of red, elemental selenium nano spheres, produced by fermentation technology, in animal tests - Prokisch, József; Babka, Beáta; Eszenyi, Péter; Sztrik, Attila; Takács, Tímea (Acta Agraria Debreceniensis, 2012)
In our experiments we tested the toxicity of Nano-Se and LactoMicroSel® compared with other organic and inorganic selenium forms, in case of a subakut animal test. We produced the Nano-Se and LactoMicroSel® by probiotic lactic acid bacteria in our laboratory. (Prokisch et al., 2010; Eszenyi et al., 2011). We mixed the inorganic selenium forms, selenite and selenate, the organic form, Sel-Plex® and our products, Nano-Se and LactoMicroSel® into the standard food of laboratory mice and we fed them for two consecutive weeks. After the extermination we observed mortality, the change of body mass,and measured the blood antioxidant capacity with FRAP method.